Optimizing the Role of Mobile Android in Improving Service Quality at BPRS Suriyah Cilacap - Nurul Fatmawati; Hidayat, Ma'ruf (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2022)
The development of increasingly sophisticsted technology makes it easier for finalcial institutions to utilize this technology in product to development and service quality at banks. BPRS Suriyah Cilacap has many services to support service operations at the bank, one of which is the android mobile service which is widely used by customers because it makes it easier for users to carry out transaction activities at the bank. The type of research used is field research conducted with informants. This study uses a qualitative method using a descriptive approach. The data sources of this study come from primary data and secondary data obtained through observation, interviews, documentation, websites, journal literature and bppks in order to obtain information and evidence in the research process. The results of this study regarding the process of optimizing the role of mobile android in improving the quality of services that have been completely optimal although there are still obstacles in their use. The android mobile service process by entering the service system and entering the customer’s name and data then input the nominal amount to be deposited by the customer and wait for the receipt or note to finish printing. In addition, the obstacles and solutions in using android mobile services at Suriyah BPRS are the service system that often has errors and disturbances when uploading transaction deposits made per day and the absence of mobile banking services in supporting the diverse needs of customers, the solution is to report to the office IT to be assisted if there are still problems and by trying to implement mobile banking services to support customer needs and many banks have used it.